Psychophysiological Reactivity Profiles of Partner-Violent Men With Borderline or Psychopathic Personality Features: the Role of Empathy - Armenti, Nicholas A. (International journal of offender therapy and comparative criminology, 2018)
Borderline and psychopathic features have been linked to unique psychophysiological reactivity profiles. Studies have suggested that levels of psychophysiological reactivity for partner-violent men cannot be attributed to personality features alone. This study tested cognitive and affective empathy as moderators of relations between borderline personality, Factor 1 psychopathy, and psychophysiological reactivity using a community sample of 135 male participants and their female partners. Cognitive empathy moderated the relation between borderline personality features and heart rate reactivity. Affective empathy moderated the relation between Factor 1 psychopathy features and heart rate reactivity. However, directions of these interactions were contrary to original predictions. Understanding unique empathy deficits may be beneficial for identifying ways to minimize relationship conflict, manage arousal, and decrease violence.